1996
DOI: 10.1007/bf00203774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β2-adrenoceptor agonists on plasma potassium and cardiopulmonary responses on exercise in patients with chronic obstructive pulmonary disease

Abstract: When compared to salbutamol 2 mg, fenoterol 2 mg caused more marked hypokalaemia but no significant difference in cardiopulmonary response in patients with COPD during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…(Yang et al). 15 Comparing COPD patients with electrolyte disorders and those without any electrolyte imbalance on admission, there was a significant decrease in PH, PaO 2 and oxygen saturation in patients with electrolyte disorders, while there was a significant increase in PaCo 2 . This means that patients with electrolyte disorders, suffer from further deterioration in arterial blood gases than other group without any electrolyte disorders.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…(Yang et al). 15 Comparing COPD patients with electrolyte disorders and those without any electrolyte imbalance on admission, there was a significant decrease in PH, PaO 2 and oxygen saturation in patients with electrolyte disorders, while there was a significant increase in PaCo 2 . This means that patients with electrolyte disorders, suffer from further deterioration in arterial blood gases than other group without any electrolyte disorders.…”
Section: Resultsmentioning
confidence: 92%
“…17,15 Treatment with Beta 2 agonists can reduce serum magnesium levels through urinary loss or intracellular shift (Rolla, and Bucca). 18 Intravenous aminophylline therapy has been recorded to cause hypomagnesaemia, hypocalcaemia and hyponatraemia in susceptible individuals by increasing the urinary secretion of these electrolytes, this in turn may cause increased pulmonary irritability and consequently increased risk of exacerbation (Knutsen).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Use of beta 2-adrenoceptor agonists like fenoterol or salbutamol may also contribute to hypokalaemia in COPD patients. [7] Moreover, acute respiratory failure associated with hypokalaemia was found to have a high mortality rate among the COPD patients. [8] High mortality in hypokalaemia may be attributed to cardiac arrhythmias or hampered nerve-muscle conduction.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed a significantly lower Naand K levels in group II patients and both groups had lower than normal values. This can be attributed to the more use of Beta-2 agonists in the more severe cases, as these medications cause electrolytes disturbances (17) . Moreover, Goli et al, 2016 (18) found significantly lower PH in patients with electrolyte disturbance which is also present in the current study.…”
Section: Jmscr Vol||06||issue||06||page 1024-1032||june 2018mentioning
confidence: 99%